'A major lobbying effort to change and unify the excise structure in six Central American countries': How British American Tobacco influenced tax and tariff rates in the Central American Common Market - Holden Chris; Lee Kelley (BMC, 2011)
Abstract Background Transnational tobacco companies (TTCs) may respond to processes of regional trade integration both by acting politically to influence policy and by reorganising their own operations. The Central American Common Market (CACM) was reinvigorated in the 1990s, reflecting processes of regional trade liberalisation in Latin America and globally. This study aimed to ascertain how British American Tobacco (BAT), which dominated the markets of the CACM, sought to influence policy towards it by member country governments and how the CACM process impacted upon BAT's operations. Methods The study analysed internal tobacco industry documents released as a result of litigation in the US and available from the online Legacy Tobacco Documents Library at http://legacy.library.ucsf.edu/. Documents were retrieved by searching the BAT collection using key terms in an iterative process. Analysis was based on an interpretive approach involving a process of attempting to understand the meanings of individual documents and relating these to other documents in the set, identifying the central themes of documents and clusters of documents, contextualising the documentary data, and choosing representative material in order to present findings. Results Utilising its multinational character, BAT was able to act in a coordinated way across the member countries of the CACM to influence tariffs and taxes to its advantage. Documents demonstrate a high degree of access to governments and officials. The company conducted a coordinated, and largely successful, attempt to keep external tariff rates for cigarettes high and to reduce external tariffs for key inputs, whilst also influencing the harmonisation of excise taxes between countries. Protected by these high external tariffs, it reorganised its own operations to take advantage of regional economies of scale. In direct contradiction to arguments presented to CACM governments that affording the tobacco industry protection via high cigarette tariffs would safeguard employment, the company's regional reorganisation involved the loss of hundreds of jobs. Conclusions Regional integration organisations and their member states should be aware of the capacity of TTCs to act in a coordinated transnational manner to influence policy in their own interests, and coordinate their own public health and tax policies in a similarly effective way.